Corrupting Learning: Evidence from Missing Federal Education Funds in Brazil - Claudio Ferraz; Frederico Finan; Diana B. Moreira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2009)
While cross-country analysis suggests that corruption hinders economic growth, we have little evidence on the mechanisms that link corruption to long-run economic development. We provide micro-evidence on the consequences of corruption for the quality of education. We use data from the auditing of Brazil's local governments to construct objective measures of corruption involving educational block grants transferred from the central government to municipalities. Using variation in the incidence of corruption across municipalities and controlling for students', schools' and municipal characteristics, we find that corruption significantly reduces the school performance of primary school students. Students residing in municipalities where corruption in education was detected score 0.35 standard deviations less on standardized tests, and have significantly higher dropout and failure rates. We also provide evidence on the mechanisms that link corruption and mismanagement to learning and school attainment. The results are consistent with corruption directly affecting economic growth through the reduction of human capital accumulation. JEL Codes: D73, I21, H72
Keywords: 330; Korruption; Bildungsniveau; Kommunalverwaltung; Bildungsfinanzierung; Finanzausgleich; Brasilien